Improvement in Outlet Obstructive Constipation Symptoms After Vaginal Stent Treatment for Rectocele. (October 2021) - Yin, Yitong; Xia, Zhijun; Luan, Meng; Qin, Meiying
Objective . The objective is to determine the possible improvement in outlet obstructive constipation symptoms after vaginal stent treatment for rectocele. Methods . Female patients with rectocele (n = 156) accompanied with outlet obstructive constipation were selected in this study. Longo's obstructed defecation syndrome (ODS) questionnaire, rectoanal pressures, and rectal balloon expulsion (BET) were evaluated at baseline, 1 month follow-up, and 6 months follow-up. Moreover, the side effects and the potential reasons for giving up treatment were also detected. Results . Vaginal stent significantly decreased the straining intensity, shortened the straining extensity time, decreased the use of laxatives, and alleviated the symptoms of incomplete evacuation ( P < .05). The vaginal stent also increased the rectal pressure and shortened the balloon expulsion time ( P < .05). Conclusions . As an effective, feasible, and safe procedure, the vaginal stent can be recommended as a treatment of choice for rectocele combined with outlet obstructive constipation.